2018
DOI: 10.1172/jci125184
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenomic analyses associate immunological alterations with mismatch repair defects in prostate cancer

Abstract: In Table 2, the mutation for patient no. 11 in the column labeled "cDNA, aa change" is incorrect. The correct mutation is NM_002524.4:c.182A>G; NRAS p.(Q61R). The JCI regrets the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 0 publications
0
22
0
2
Order By: Relevance
“… 34 While a study suggests favourable responses to ADT, others have found that MMR-deficient patients develop castration-resistant disease earlier than the MMR-proficient ones. 35 , 36 These differences in outcomes between studies may be related to the limited number of patients included and the different assays used to detect these alterations (targeted sequencing vs. immunohistochemistry). Further studies are needed to completely elucidate the clinical implications of these and other DDR alterations in prostate cancer.…”
Section: Clinical Implications Of Ddr Gene Alterations In Prostate Camentioning
confidence: 99%
“… 34 While a study suggests favourable responses to ADT, others have found that MMR-deficient patients develop castration-resistant disease earlier than the MMR-proficient ones. 35 , 36 These differences in outcomes between studies may be related to the limited number of patients included and the different assays used to detect these alterations (targeted sequencing vs. immunohistochemistry). Further studies are needed to completely elucidate the clinical implications of these and other DDR alterations in prostate cancer.…”
Section: Clinical Implications Of Ddr Gene Alterations In Prostate Camentioning
confidence: 99%
“…In advanced prostate cancer, where two clinical trials testing response to immune checkpoint blockade in unselected patients have failed [80, 81], a report from de Bono and colleagues evaluated the diagnosis of MMRd using a variety of assays including IHC, MSI by PCR, MSI by targeted panel NGS of MMR pathway genes, and MSI by exome sequencing (WES) assay [82]. Their results showed that the PCR-based assay of MSI was more likely to give discordant (presumed false-positive) results when compared to the results of the NGS-based tests.…”
Section: Genomic Instability Neoantigens and Immunotherapy Responsementioning
confidence: 99%
“…By contrast to p110α and similar to p110β overexpression of p110γ transform cells in vitro, this process still needs upstream signaling input since mutating the Gβγ-binding site on p110γ or p101 severely affects the cell transforming efficiency [54,193]. Nonetheless, copy number gain or increased expression levels rather than mutations were associated with various patients’ tumors such as leukemia and medulloblastoma, as well as breast, liver, pancreatic, ovarian, clear-cell renal carcinoma or prostate cancer [52,152,194,195,196,197]. It is worth mentioning that recurrent mutations of the PIK3CG gene were reported to occur in a considerable number of patients suffering from biliary cancer, metastatic prostate cancer or renal cell carcinoma although the functional consequences remain to be established [50,198,199,200].…”
Section: Biological Functions Of Pi3kγmentioning
confidence: 99%